2020
DOI: 10.3390/ijms21041380
|View full text |Cite
|
Sign up to set email alerts
|

Using Transcriptomic Analysis to Assess Double-Strand Break Repair Activity: Towards Precise in Vivo Genome Editing

Abstract: Mutations in more than 200 retina-specific genes have been associated with inherited retinal diseases. Genome editing represents a promising emerging field in the treatment of monogenic disorders, as it aims to correct disease-causing mutations within the genome. Genome editing relies on highly specific endonucleases and the capacity of the cells to repair double-strand breaks (DSBs). As DSB pathways are cell-cycle dependent, their activity in postmitotic retinal neurons, with a focus on photoreceptors, needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…While top indel insT in iPSC-CMs was a consequence of cNHEJ (active in both proliferative and non-proliferative cells), del9 in iPSCs most likely resulted from MMEJ, a DNA double-strand break repair mechanism known to be predominantly active in proliferating cells during S and G2 phase. 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…While top indel insT in iPSC-CMs was a consequence of cNHEJ (active in both proliferative and non-proliferative cells), del9 in iPSCs most likely resulted from MMEJ, a DNA double-strand break repair mechanism known to be predominantly active in proliferating cells during S and G2 phase. 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…One such study conducted recently indicates that AAV2-7m8 has superior transduction, possibly due to higher infectiousness and effective activation of secondary receptors [ 69 ]. Most genome editing techniques rely on highly specific endonucleases and the capacity of a cell to repair double-stranded breaks (DSB): since DSBs are cell-cycle dependent, it is even more important to examine the present gene editing options in vitro before starting clinical trials [ 70 ].…”
Section: The Rise Of Retinal Organoids–technical Development and Amentioning
confidence: 99%
“…Importantly, the transcriptional signatures of the DNA repair pathways in the retina have been recently characterized using transcriptomic analyses of in vivo and in vitro models ( Pasquini et al, 2020 ). This study showed that photoreceptors, as post-mitotic cells, display low expression levels of HDR pathway components; whereas NHEJ and MMEJ pathway factors are expressed and active in these cells.…”
Section: Genetic Therapies For Treating Irds: From Gene Augmentation mentioning
confidence: 99%